Pemberdayaan Masyarakat UMKM dalam Pemasaran Produk Lokal Batam - Friadi, John; Diana Titik Windayanti; Abdul Malik Made (Penerbit Goodwood, 2024)
Purpose: Empowering MSMEs to increase the marketing of local products to become a catalyst for MSME growth and improve the regional economy as a diverse economic center. Methodology: The implementation of the community service program includes the preparation stage, survey stage, e-commerce platform development stage, training and mentoring stage in implementing the e-commerce platform, and monitoring and evaluation stage of the implementation of the community service program as a whole Results: The development of e-commerce platform applications, opening of batik product marketing distribution networks to reduce logistics and shipping costs, strengthening knowledge about markets and marketing, and increasing digital skills capacity. Limitations: The expansion of market reach is expected to increase the sales potential of more UMKM Cindur Batik products, so that the income obtained is maximized and community empowerment increases. When income increases, UMKM communities will be better able to maintain the sustainability of their businesses and help improve the Indonesian economy. Contribution: The contribution of community empowerment service in increasing the marketing of local Batam products at the Cindur Batik UMKM is by forming an UMKM consortium to increase joint strength in the distribution and sales of UMKM products, in this case the Batik UMKM, to overcome the problem of limited access to local and regional markets.